An extended multiple-strut model to estimate infill effects on multi-storey steel frames with different connection rigidities. (April 2021) - Pashaie, Mohammad Reza; Mohammadi, Majid
Abstract: The experiences of previous earthquakes highlight the necessity of modelling infills in the analysis of structures. In the 2017 Sarepol-e-Zahab earthquake, infills were the cause of most damages inflicted on structures. In this paper, a previously proposed multiple-strut model for infills in steel frames with rigid connections is further developed for non-rigid connections. A comprehensive sensitivity analysis is carried out on the single-storey, single-bay frames with pinned and semi-rigid connections. The parametric study includes the evaluation of the aspect ratio, friction coefficient, and infill-to-column relative stiffness in the models. The global and local effects of infills on multi-bay infilled frames are also explored. This study also presents an investigation of the application of the proposed model in multi-storey infilled frames. Finally, a method consisting of a few simple steps is proposed to optimally take into account the effects of infill panels in multi-storey frames. The accuracy of the model in predicting the base shear and the internal forces of the components of the frame shows that it is a reliable model in the retrofit and seismic design of the steel structures.